Second trimester vaginal Candida colonization among pregnant women attending antenatal care in Bukavu, Democratic Republic of the Congo: prevalence, clinical correlates, risk factors and pregnancy outcomes - Mulinganya, Mulumeoderhwa Guy; De Keyser, Karen; Mongane, Irenge Jules; Kampara, Mirindi Freddy; De Vulder, Annelies; Boelens, Jerina; Duyvejonck, Hans; Hendwa, Erick; Kujirakwinja, Bisimwa Yvette; Bisimwa, Balaluka Ghislain; Rodriguez, Antonio; Vaneechoutte, Mario; et al. (Frontiers in Global Women's Health, 2024)
Introduction Vaginal Candida colonization (CC) can lead to vulvovaginal candidiasis, the second most prevalent vaginal condition worldwide, and has been associated with adverse birth outcomes. However, no data on CC in the Democratic Republic of the Congo are available. We investigated the prevalence, Candida species, clinical correlates, risk factors and pregnancy outcomes in women with CC in the second trimester of pregnancy. Material and methods In Bukavu, the Democratic Republic of the Congo, pregnant women were recruited during antenatal care between 16 and 20 weeks of gestation from January 2017 to October 2017 and followed until delivery. Sociodemographics, sexual behavioral, hygienic and clinical characteristics, microbiological data and pregnancy outcomes were collected. Candida detection and speciation was performed with microscopy (Gram-stained smears and wet-mount) and/or quantitative PCR. Multivariate regression models were used to estimate the different associations with CC. Results The prevalence of CC by wet mount, microscopy of Gram-stain smears and qPCR was 27.9%, 28.1% and 38.2%, respectively. C. albicans was the most prevalent Candida species (91.0%). Previous genital infections, an intermediate vaginal microbiota, bacterial vaginosis, and the use of pit toilets were risk factors for CC. Clinically, CC was associated with itching only. Women with CC had twice the odds for preterm birth, if Candida concentration was high, the odds were four times higher. Conclusions In Bukavu, the Democratic Republic of the Congo, the prevalence of CC was high and associated with microbiological and modifiable risk factors. Screening and treatment for CC during antenatal care should be investigated as a possible strategy to reduce preterm birth.